Risk factors for multiple organic dysfunctions syndrome in burnt children. - Elvira Maria Martinez Barreto; Jorge González Mendoza (Medisur)
Background: The creation of intensive care units allows extending the life of patients with serious conditions, including multiple organic dysfunction syndromes. Objective: To determine the clinical variables and laboratory variables that are risk factors for multiple organic dysfunction syndromes in burnt children. Methods: Analytical, retrospective study of case series including burnt patients between 0 and 5 years hospitalized in the university Paediatric Hospital “Paquito González” in Cienfuegos and classified as: serious, very serious, critical, and extremely critical. This study was developed from January 1st, 2000 to December 31st, 2005. The considered systems for dysfunction diagnosis were: respiratory, cardiovascular, gastrointestinal, hepatic, renal, metabolic, central nervous system, hematologic, immunologic, and wounds healing. Data was processed by bivariate analysis of independent variables in relation with the dependent variable, to model a response variable of the syndrome occurrence (or not). The multivariate analysis of logistic regression was used. Results: 34 children developed the syndrome 44, 2 %). Significant variables linked to this syndrome were: seriousness of the injuries, serum potassium, blood creatinine, leukocyte counting, and cardiac rhythm. Conclusions: After five days of research development, a group of factors was identified proving risky for the development of multiple organic dysfunctions in burnt children.